2017
DOI: 10.1002/celc.201700572
|View full text |Cite
|
Sign up to set email alerts
|

Freeze Drying as a Novel Approach to Improve Charge Transport in Titanium Dioxide Nanorod Arrays

Abstract: Ordered TiO2 nanostructure arrays, such as hydrothermal nanorod arrays (NRAs) and anodic nanotube arrays, have attracted great attention in solar cells, photocatalysis, and so on, mainly owing to their vertically aligned 1D architectures. However, the device performances are limited by their poor electronic properties, owing to the morphology collapse and surface adsorbates. In this work, a novel freeze‐drying technique has been used to post‐treat hydrothermal TiO2 NRAs. The freeze‐drying treatment not only le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The architecture of the photoelectrode greatly influences the performance of PEC devices as it determines its surface area, charge transport, and collection capability. , Vertically aligned TiO 2 nanowire (NW) arrays is one of the ideal constructions for loading noble metal NPs due to their superiority on charge transport properties. However, well-separated rutile TiO 2 NW arrays have been limited to lengths of about 3–4 μm, and further increasing the length leads to fusion at their roots. , This, in turn, not only reduces the available surface area for noble metal NP loading but also decreases the charge transport properties, resulting in low utilization of the noble metal NPs. In the current study, we adopted a solvothermal method to fabricate long and well-separated single-crystal rutile TiO 2 NW arrays and then uniformly decorated the surface with Au NPs to form the Au-TiO 2 photoanode.…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of the photoelectrode greatly influences the performance of PEC devices as it determines its surface area, charge transport, and collection capability. , Vertically aligned TiO 2 nanowire (NW) arrays is one of the ideal constructions for loading noble metal NPs due to their superiority on charge transport properties. However, well-separated rutile TiO 2 NW arrays have been limited to lengths of about 3–4 μm, and further increasing the length leads to fusion at their roots. , This, in turn, not only reduces the available surface area for noble metal NP loading but also decreases the charge transport properties, resulting in low utilization of the noble metal NPs. In the current study, we adopted a solvothermal method to fabricate long and well-separated single-crystal rutile TiO 2 NW arrays and then uniformly decorated the surface with Au NPs to form the Au-TiO 2 photoanode.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 14 , 15 During the conventional bottom-up growth process, synthesis variations to increase the length generally result in the widening of the NWs and subsequent fusion at their roots. 16 – 18 This, in turn, reduces the aspect ratio, increases the structural disorder and reduces the charge transport; 19 , 20 experimental results shown in ESI Fig. S1 † indicate that the diffusion coefficient of bundled TiO 2 NWs is over one order of magnitude lower than that of well-separated ones.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong and coworkers used a freeze-drying technique to post-treat hydrothermally grown TiO 2 nanowire arrays. [139,140] They demonstrated that freeze-drying not only led to well-preserved nanoarray morphology but also resulted in the complete removal of adsorbed chlorine from the TiO 2 surface. They obtained a better electron collection coefficient on the treated nanowire arrays for use in solar cells.…”
Section: Charge Transport In Single-crystal Nanowire Array-based Photoelectrodesmentioning
confidence: 99%